2014
DOI: 10.1016/j.bbmt.2014.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Frequent Human Herpesvirus-6 Viremia But Low Incidence of Encephalitis in Double-Unit Cord Blood Recipients Transplanted Without Antithymocyte Globulin

Abstract: Cord blood transplantation (CBT) is a known risk factor for human herpesvirus-6 (HHV-6) infection. We analyzed the nature of HHV-6 infections in 125 double-unit CBT recipients (median age 42 years) transplanted for hematologic malignancies with calcineurin-inhibitor/ mycophenolate mofetil prophylaxis and no anti-thymocyte globulin (ATG). One-hundred and seventeen (94%) patients reactivated HHV-6 by quantitative plasma PCR (median peak 7,600 copies/mL, range 100-160,000) at a median of 20 days (range 10-59) aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
1
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 57 publications
2
39
1
5
Order By: Relevance
“…11,27 Methods of GvHD prophylaxis were shown to be associated with the development of HHV-6 encephalitis in CBT; previous reports have supported the clinical plausibility of such a relationship. An inflammatory milieu early after allo-HSCT, such as pre-engraftment immune reaction, 11 engraftment syndrome 28 and GvHD, 12,28 represents risk factors for subsequent development of HHV-6 encephalitis.…”
Section: Discussionmentioning
confidence: 96%
“…11,27 Methods of GvHD prophylaxis were shown to be associated with the development of HHV-6 encephalitis in CBT; previous reports have supported the clinical plausibility of such a relationship. An inflammatory milieu early after allo-HSCT, such as pre-engraftment immune reaction, 11 engraftment syndrome 28 and GvHD, 12,28 represents risk factors for subsequent development of HHV-6 encephalitis.…”
Section: Discussionmentioning
confidence: 96%
“…4,5 HHV-6 encephalitis develops concomitant to peak blood HHV-6 DNA. 3,5,7,8 Some studies in which blood levels of HHV-6 DNA have been monitored have shown a correlation between HHV-6 reactivation and the development of HHV-6 encephalitis, 1,[3][4][5][6][7][8]56 but others have failed to demonstrate such associations. 2,57,58 The reasons for these divergent results may be because of the low incidence of HHV-6 encephalitis even in patients with HHV-6 reactivation.…”
Section: Hhv-6 Reactivation and Hhv-6 Encephalitis: We Know Hhv-6 Reamentioning
confidence: 99%
“…A recent meta-analysis of 19 papers found that HHV-6B encephalitis was significantly higher in CBT recipients (8.3%) than other allogeneic HCT recipients (0.5%) [19 •• ]. In a prospective cohort of CBT recipients transplanted without antithymocyte globulin, reactivation was documented in 94% of patients [29]. The authors reported a low level (1.6%) of encephalitis and no association with clinical outcomes, but almost 1/3 of patients received preemptive antiviral therapy.…”
Section: Human Herpesvirus 6bmentioning
confidence: 99%